Penyiapan dan Publikasi Artikel Ilmiah bagi Guru-Guru MGMP Bahasa Indonesia di Kabupaten Trenggalek - Ardhian, M.Hum., Dr. Dany; Wahyuni, Lilik; Zakiyah, Millatuz (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The publication of scientific works is a crucial aspect in the development of knowledge and career advancement, especially for teachers. Teachers are not only expected to teach, but also to produce scientific works that contribute to the development of science. Although important, many teachers are reluctant to publish because it requires time, energy, and adjustment to scientific journal standards. However, according to Minister of National Education Regulation No. 35 of 2010, publishing scientific works is a requirement for promotion to a higher rank, such as from Grade IVa to IVb. The challenges teachers face in publishing include a lack of information about relevant journals, difficulties in using submission systems like Open Journal System (OJS), and the limited number of journals managed by teachers themselves. Universities play a crucial role in supporting and assisting teachers by providing information, training, and technical assistance related to scientific publications. This community service program was conducted over three months (July–September 2023) and consisted of the following stages: (1) Establishing communication with the Indonesian Language Teachers' Association (MGMP) of Trenggalek District, (2) Collecting articles (84 articles were submitted via Google Forms), (3) Selecting articles, (4) Reviewing articles, (5) Conducting a scientific article writing training session (on July 25, 2023, attended by 60 participants), and (6) Preparing teachers' scientific articles for publication. This program is not only expected to provide tangible benefits for teachers in developing their publication skills but also to strengthen partnerships between universities and schools in efforts to improve the quality of education and research. Keywords: Indonesian Language MGMP Teachers; Trenggalek Regency; Scientific Article Publication